Hierarchy of Need in Midnight Sun: The Ways of Portraying - Rahmawati, Ivana Salsabila (NOBEL: Journal of Literature and Language Teaching, 2026)
The research explores how Katie progresses through these stages through a descriptive qualitative approach. This study analyzes Katie’s psychological development using Maslow’s Hierarchy of Needs, which consists of five levels: physiological needs, safety needs, love and belongingness, esteem, and self-actualization. The film highlights the importance of human relationships in psychological well-being, illustrating Maslow’s theory that love and belonging are essential for emotional and personal development.